The Effect of Date Fruit Consumption on Spontaneous Labor - Maryam Yousefy Jadidi; Nourossadat kariman; Sara Jam Bar Sang; Hassan Lari (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Background and Objectives: Post term pregnancy is one of the important problems in obstetrics which are associated with both mother and fetus outcomes, such as labor induction, prenatal morbidity and mortality and increased rate of cesarean delivery. The aim of this study was to determine the effect of consumption date fruit on spontaneous labor in nulliparous women in selected research centers was carried out in 1392. Materials and Methods: This study was a randomized clinical trial was performed on 110 nulliparous pregnant women with gestational age of 38 weeks of pregnancy. Volunteer pregnant women were randomly allocated into two groups: the intervention and one control group. The intervention group consumed 49 dates for one week,(7dates daily) but there was normal care in the control group. Research tools including interview, observation, examination and food record. Collected Data were analyzed using computer software 18spss and descriptive and quantitative statistical tests . Significance level of p<0/05 was considered. Results: The findings showed that the average length of pregnancy in the intervention and control groups was 39/4 ± 16 and 40/12 ± 21 weeks, respectively. Between the intervention and control groups was significant difference in the onset of labor (P <0/001). Dilatation and effacement of the cervix at the time of admission in the intervention group was significantly higher than the control group (P=0/001, P=0/0001). Conclusion: This study showed that the consumption of date fruit can be an effective way to prevent prolonged pregnancy and reduce the need for induction. Keywords:  Date palm, spontaneous labor, Post term pregnancy, labor induction For downloading the full-text of this article please click here.